ANALISIS PENGATURAN SUBSTANSI KEWENANGAN ISTIMEWA DALAM PERATURAN DAERAH ISTIMEWA DAERAH ISTIMEWA YOGYAKARTA - Maheswara, Giovanni Battista; Rauta, Umbu; Margaretha, Lagasakti Parwati (Penerbit Universitas Atma Jaya Yogyakarta, 2024)
The Special Region of Yogyakarta is one of the provinces in Indonesia that has a privileged status so that it has a certain authority in running its government. This authority is affirmed in Article 7 paragraph (2) of the Law of the Republic of Indonesia Number 13 of 2012 concerning the Privileges of the Special Region of Yogyakarta which includes matters such as procedures for filling out the positions, positions, duties, and authorities of the Governor and Deputy Governor; DIY Regional Government Institutions; Culture; Land; and Layout. These five powers are then directly implemented into the Special Regional Regulation. The problem of this research is how is the substance of the Special Authority of DIY which is regulated by the Perdais? And whether of the 5 kinds of special authority mentioned in Article 7 paragraph (2) of the Law of the Republic of Indonesia Number 13 of 2012 concerning the Privileges of the Special Region of Yogyakarta there are only 5 Special Regional Regulation or can it be reduced to more than 5 Special Regional Regulation?. The research method that will be carried out is a normative study, namely research that focuses on positive legal norms and laws and regulations. The approach method used is the history of law; sociology of law and legal politics.